Cadaveric kidney allograft transplantation using the Da Vinci robotic surgical system. Initial experience in the Russian Federation - V. L. Medvedev; V. A. Porkhanov; K. E. Chernov; S. N. Volkov; G. A. Palaguta; O. V. Arepyeva; E. V. Gerdel (Вестник трансплантологии и искусственных органов)
Kidney transplantation is the treatment of choice for patients with end-stage renal disease. In order to reduce the number of postoperative complications following open surgeries, a number of clinics in the USA and Europe are currently developing robot-assisted surgical techniques. Studies have shown that robotic surgery facilitates kidney transplantation under optimal ergonomic position for the surgeon, with functional results and patient safety comparable to those obtained under an open approach. We herein present our initial experience (in the Russian Federation) on heterotopic cadaveric kidney transplantation by laparoscopic surgery using the Da Vinci robotic surgical system.